2020
DOI: 10.3390/cancers12040969
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic Intraperitoneal Chemotherapy for Primary or Recurrent Adrenocortical Carcinoma. A Single Center Study

Abstract: Background. This study explores the impact of Hypertermic Intra PEritoneal Chemotherapy (HIPEC) on adrenocortical carcinoma (ACC) management through a safety analysis completed by a preliminary evaluation of survival performances. Methods. Retrospective chart review of 27 patients submitted to surgical treatment completed by HIPEC for primary (SP, 13 patients) or recurrent (SR, 14 patients, 17 treatments) ACC. Safety was evaluated by means of procedural morbidity and mortality. Survival performances included m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…When HIPEC was used prophylactically at the initial operation for the primary tumor, there was peritoneal recurrence in 1 of 13 patients at a median follow-up of 25 months. Peritoneal recurrence was 68% for recurrent disease at a median follow-up of 30 months [ 56 ]. This is similar to the National Institutes of Health (NIH) experience treating recurrent ACC with HIPEC, where recurrence was 70% at a median follow-up of 23 months and 2/9 patients died from disease progression.…”
Section: Current Treatment Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…When HIPEC was used prophylactically at the initial operation for the primary tumor, there was peritoneal recurrence in 1 of 13 patients at a median follow-up of 25 months. Peritoneal recurrence was 68% for recurrent disease at a median follow-up of 30 months [ 56 ]. This is similar to the National Institutes of Health (NIH) experience treating recurrent ACC with HIPEC, where recurrence was 70% at a median follow-up of 23 months and 2/9 patients died from disease progression.…”
Section: Current Treatment Approachesmentioning
confidence: 99%
“…This is similar to the National Institutes of Health (NIH) experience treating recurrent ACC with HIPEC, where recurrence was 70% at a median follow-up of 23 months and 2/9 patients died from disease progression. As with HIPEC in general, there was high morbidity in both studies, ranging from 40–70% [ 56 , 57 ]. More data are needed to make firm conclusions about the use of HIPEC in the prophylactic setting, but the limited data available have shown it is ineffective for recurrent disease.…”
Section: Current Treatment Approachesmentioning
confidence: 99%
“…One paper presents the results of a single institution experience regarding the potential efficacy of hypertermic intra-peritoneal chemotherapy (HIPEC) after radical surgery. The results show that this therapeutic procedure might result in long-term disease control, particularly in treatment-naïve patients [ 24 ].…”
mentioning
confidence: 99%
“…A recent study demonstrates that hyperthermic intraperitoneal chemotherapy immediately following primary resection has been shown to improve local recurrence, though is limited by significant morbidity and requires careful candidate selection. Furthermore, it has not yet demonstrated clear benefit in treating recurrent disease [9]. In patients with unresectable locally advanced or metastatic disease, Laganà et al (2020) have shown some long-term benefit in EDP-M chemotherapy (etoposide, doxorubicin and cisplatin plus oral mitotane), including the eventual possibility of surgically excising residual disease following treatment response [10]; however, this similarly comes at the cost of systemic chemotherapy with significant toxicity.…”
mentioning
confidence: 99%